How to achieve the energy transition taking into account the efficiency of energy resources consumption - Mykhailyshyn Khrystyna; Polyanska Alla; Psyuk Vladyslav; Antoniuk Olena (E3S Web of Conferences, 2024)
The study explores the transformation of energy resource consumption centered on energy efficiency within the global energy transition framework. The growing global energy demand, driven by industrialization, urbanization, and rising living standards, has led to increased fossil fuel consumption. This, in turn, contributes to higher greenhouse gas emissions, global warming, and other adverse environmental impacts. The study emphasizes the efforts of developed nations to curb these emissions, particularly by expanding renewable energy use, and notes the declining share of coal and other fossil fuels in national energy balances. The Energy Transition Index (ETI) is introduced as a measure of countries’ progress in advancing the energy transition, including efforts to enhance energy efficiency and mitigate environmental harm. The study also highlights Ukraine’s challenges in energy supply due to military conflict and infrastructure damage, underscoring the critical role of energy efficiency in rebuilding the country’s energy system and securing its energy future. Energy efficiency is identified as a key strategy for reducing dependence on fossil fuels, decreasing energy imports, and bolstering the economy’s resilience to external pressures.